Tricholosporum, a newly recorded genus of Agaricomycetes in China - Liu, Yuan Chao; Liu, Pu; Hu, Hui Ping; Li, Dan; Li, Yu (Phytotaxa, 2016)
One species of Tricholosporum was collected from HunHeyuan Nature Reserve in Liaoning Province, northeast China. It is a newly recorded genus to China. Descriptions, illustrations of T. porphyrophyllum, a new record from China, are given based on collected specimens, while the phylogenetic analysis based on ITS, nlsu rDNA and rpb2 sequences were studied to determine the taxonomic status of this genus and discussed the relationship between this genus and other genera of Tricholomataceae.